Forms, quantity/intensity ratio and bioavailability of potassium in different Latosols (Oxisols) - Silva, Ivo Ribeiro da; Neto, Antonio Eduardo Furtini; Fernandes, Luiz Arnaldo; Curi, Nilton; Vale, Fabianio Ribeiro do (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to quantify the potassium forms in four Latosols (Oxisols) from Campos das Vertentes, MG, Brazil, physiographical zone, influenced by different parent materials, and to evaluate their capacity to furnish potassium to two native forest species (Peltophorum dubium and Senna multijuga) and to corn (Zea mays). The experiment was conducted in greenhouse conditions at Soil Science Department of Universidade Federal de Lavras, in Lavras, MG, Brazil, in a completely randomized design, with six replications. For the characterization of potassium forms (total, non-exchangeable, available, exchangeable and in solution) and determination of the quantity/intensity ratio, soil composite samples from superficial (0-20 cm) and subsuperficial (20-60 cm) layers were utilized. The results showed that, among the evaluated K forms, only the total K was related to the parent material, being the highest values observed for the soils influenced by pellitic rocks. The exchangeable and the available K were the forms which more contributed to the total K. The in solution K presented elevated concentration in the four soils. For the Peltophorum dubium and Senna multijuga, the Dark-Red and Una Latosol revealed adequate amounts of K for the initial growth of these species, while for the corn there was response to this nutrient application.
Keywords: Peltophorum dubium; Senna multijuga; Zea mays; plant soil relations; nutrients; soil fertility